Macroeconomic Implications of Real Exchange Rate Targeting in Developing Countries - Montiel, Peter (IMF Working Papers; Working Paper, 1991)
This paper analyzes the macroeconomic effects of a variety of exogenous and policy-induced real disturbances when the authorities target the level of the real exchange rate. It first discusses the implications--particularly for inflation and the current account--of targeting the rate at an 'overdepreciated' level. The paper then examines the dynamic response of both output and inflation to a number of shocks. Further applications of the model, particularly as regards fiscal explanations of inflation, high-inflation plateaus, and money-based stabilization programs, are also considered.